Cloud Computing Adoption in the Financial Banking Sector- A Systematic Literature Review (2011-2021) - Adwan, Ehab Juma; Alsaeed, Bader Ali (International Journal of Advanced Science Computing and Engineering, 2022)
Scholarly research works on the adoption of Cloud Computing (CC) have recently emerged with the technology’s importance for organizations at a fast pace. Despite the numerous advantages of CC adoption for financial institutions (FI) in terms of storage cost mitigation, computation higher increase, and information access higher access rates from any place, Banking’s CC adoption executives and practitioners are badly seeking to obtain trustworthy recipes of how to utilize CC adoption frameworks to transform banks operations to cloud. In this vein and based on a systematic literature review (SLR) method, we conducted a review of 370 empirical studies from 2011 to 2021, downsized the studies to 27 directly relevant papers to reveal 14 frameworks, methods, models, or strategies of CC adoption in Banking sectors in 14 countries, and compared the findings across studies in terms of the utilized frameworks, methods, models, or strategies.